An analysis of the impact of ASEAN's logistics performance on trade flows using linear and non-linear methods in an augmented gravity model - Barton Sy; Stephen Jun Villejo; Rutcher Lacazav (Logistics Research, 2020)
Logistics in trade has a pivotal role in the economic development and in the competitiveness of countries. This study aims to provide a strong empirical evidence in linking logistics performance with trade flows in the ASEAN region using panel data methods in an augmented gravity model. The Logistics Performance Index (LPI) collected by World Bank is the metric used for logistics performance whose impact on ASEAN's aggregate and sectoral trade using the priority sectors from 2007 to 2016 is explored. For sectoral trade, the data is zero-inflated with a strong evidence of heteroscedasticity. Hence, non-linear methods were used, namely, Poisson Pseudo Maximum Likelihood method, Feasible Generalized Least Squares method, and the Heckman Two-step procedure, while for overall trade, the usual panel estimation methods were used. The results showed that logistics performance has a strong positive association with trade value, both for aggregate trade and for trade in each of the priority sectors. The outputs of the LPI framework, particularly, timeliness, tracking and tracing, and ease of arranging international shipments are relatively more important indicators of logistics performance in increasing trade value.
Keywords: 650; gravity model; ASEAN trade; logistics; panel data